DIFFICULT MASK VENTILATION RESCUED BY A PEDIATRIC FACEMASK - Govil, Nishith; Singh, Girish Kumar; Chandra, Prakash; Ittoop, Amanta Lucy (Bali Journal of Anesthesiology, 2018)
Anesthetic challenges arises in securing airway due to difficult mask ventilation because of obstructed nasal passage and unanticipated intraoral extension by a tumour mass leading to difficult intubation also. This sometime lead to the dreaded path of âCannot Intubate & Cannot Ventilateâ. We are describing a successfully managed case of ossifying fibroma arising from the maxilla causing difficulty in ventilation with the help of pediatric circular facemask and airway.